Comparative Analysis of Lower Back Pain and Phantom Pain in Unilateral Lower Limb Amputees: A Study on Amputee Football Players vs. Non-Athletes - Aleksandra Jóźwik; Agnieszka Wnuk-Scardaccione; Jan Bilski (Medicina)
Background and Objectives: Amputation poses a significant clinical and therapeutic challenge, with over 90.0% of amputations involving the lower limbs, of which 75.0% are associated with diabetes and peripheral artery disease. Individuals with lower limb amputations often experience secondary disabilities. This study aimed to compare the frequency and intensity of lower back pain and phantom pain in individuals with unilateral lower limb amputations who were amputee football players with those who did not participate in adaptive sports. Materials and Methods: This study included 30 men who had undergone unilateral lower limb amputation and were divided into two groups: 15 amputee football players and 15 men who did not participate in adapted sports. Testing included proprietary surveys, questionnaires, the Oswestry Disability Index (ODI), and the visual analog scale (VAS) for pain intensity. The Amputee Mobility Predictor (AMPnoPRO) was used to assess motor function. Statistical analysis was performed using Statistica software (Version 13, StatSoft, Inc., Tulsa, OK, USA) by applying Student’s t-test, the Mann–Whitney U test, correlation coefficients, and analysis of covariance (ANCOVA). Phantom pain was reported in 53.3% of individuals in the study group and in 66.7% of individuals in the control group, with average median pain intensities of 5.5 (IQR: 2) and 5.5 (IQR: 3), respectively. Lower back pain was significantly higher in the control group (86.7%) than for the football players (33.3%), with median pain intensities of 4 (IQR: 2) and 3 (IQR: 2), respectively. The median disability score was 3 (IQR: 3) in the player group and 10 (IQR: 7) in the control group. The median score in the amputee football player group was 35 (IQR: 2), while that in the control group was only 18 (IQR: 19). Conclusions: Amputee football training did not have a significant impact on the frequency or intensity of phantom pain but was associated with lower occurrence and intensity of pain in the lower back. The players exhibited significantly better motor function and lower levels of disability. Preoperative limb pain was a significant risk factor for phantom pain in the study group. Adaptive sports can not only support the development of motor and social skills but also contribute to reducing the severity of lower back pain, which leads to a decrease in the level of disability.